A new sedge species Mapania sekudaniana (Cyperaceae) from Sarawak, Malaysia - Ivy Geradlyn Nangan, Melana; Zinnirah, Shabdin; Awang Ahmad Zahid, Awang Baim; Meekiong, Kalu; Freddy Yeo, Kuok San (Malayan Nature Society, 2023)
: A new sedge species Mapania sekudaniana Melana, Shabdin & Meekiong sp. nov. is described and illustrated herein. This new species is closely similar to Mapania longiflora C.B. Clarke, but can be differentiated by its single spike and abruptly narrowed leaf apex.